STUDY ON ANTIBACTERIAL EFFECTS OF SEVERAL VIETNAMESE MEDICINE PLANTS AND THEIR RELATIONSHIPS WITH POLYPHENOL CONTENTS - THANH VAN NGUYEN; HAI THANH NGUYEN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Our study evaluated the inhibitory effects of 13 plant materials on bacterial growth, so as to explain their traditional uses in bacterial infections. In addition, the correlation between antibacterial effects of plants and the polyphenol contents or antioxidant activities was also verified to investigate if these properties were responsible for the plant antibacterial effects. Methods: We tested extracts with 20 bacterial strains purchased from Japan Veterinary Products Association (JVPA, Tokyo, Japan) and also the Escherichia coli (E. coli) and Streptococcus suis (S. suis) strains that we had previously isolated from livestock. After polyphenol contents and antioxidant activities were measured, we examined their correlations with antibacterial effects. Results: The results showed that all extracts exerted inhibitory effects on tested bacteria and at different levels. Among all of samples, betel and mother rhizome of turmeric showed the strongest effects and also exerted inhibition on antibiotic-resistant E. coli and S. suis bacteria. In addition, direct and significant correlations between antibacterial effects’ and polyphenol content’s values were established and thus demonstrating that antibacterial effects of plants were attributable, at least in part, to the presence of polyphenol compounds. Conclusions: Our study demonstrated the antibacterial effects of 13 plant materials and, therefore, partly gives pharmacological basis to explain their traditional uses in diseases associated with bacterial infections. In addition, as betel and mother rhizome of turmeric showed the highest effects, we suggested that they might serve as the most promissory candidates for bacterial treatment. However, follow-up researches are still required to assess their potentials.